Expansion of Human Hematopoietic Stem/Progenitor Cells on Decellularized Matrix Scaffolds. (6th February 2014) - Tiwari, Abhilasha; Tursky, Melinda L.; Kirkland, Mark A.; Pande, Gopal
Abstract: Umbilical cord blood (UCB) is one of the richest sources for hematopoietic stem/progenitor cells (HSPCs), with more than 3000 transplantations performed each year for the treatment of leukemia and other bone marrow, immunological, and hereditary diseases. However, transplantation of single cord blood units is mostly restricted to children, due to the limited number of HSPC per unit. This unit develops a method to increase the number of HSPCs in laboratory conditions by using cell‐free matrices from bone marrow cells that mimic 'human‐body niche‐like' conditions as biological scaffolds to support the ex vivo expansion of HSPCs. In this unit, we describe protocols for the isolation and characterization of HSPCs from UCB and their serum‐free expansion on decellularized matrices. This method may also help to provide understanding of the biochemical organization of hematopoietic niches and lead to suggestions regarding the design of tissue engineering–based biomimetic scaffolds for HSPC expansion for clinical applications. Curr. Protoc. Stem Cell Biol . 28:1C.15.1‐1C.15.15. © 2014 by John Wiley & Sons, Inc.